ANALISIS STRATEGI PEMASARAN UMKM BATIK SEMBORO DENGAN METODE STP (SEGMENTATION, TARGETING, POSITIONING) UNTUK MENINGKATKAN DAYA SAING - Susanto, Yanuar Bagus; Suharto, Akhmad; Puspitadewi, Ira (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aims to find out how effective the implementation of the Segmenting, Targeting, and Positioning (STP) strategy implemented by Batik Semboro is in increasing its competitiveness. In this study, researchers used descriptive analysis methods with a qualitative approach, which is a research method for describing, summarizing various social phenomena that exist in society, as well as drawing surface social reality as characteristics, characters, traits, models, signs or descriptions of phenomena. Data collection techniques used by researchers are observation, interviews, and documentation using triangulation techniques. The procedure in this study uses data analysis techniques according to Miles and Huberman including data reduction, data display, and drawing conclusions. The results of this study indicate that consumers of batik are dominated by female consumers aged 20-30 years with an undergraduate degree who earn less than Rp. 1,000,000.